Sintering effect on boron based Bioglass doped composites of bovine hydroxyapatite - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2012)
The use of bovine hydroxyapatite (BHA) provides an alternative approach in bioceramics based on natural resources, time and cost efficiency. In this study, composites of calcinated bovine derived BHA were utilized. These were doped with known quantities of boron based bioglass (5 and 10 wt. %) and a range of composites were prepared at selected sintering temperatures (1000-1300 degrees C). The resulting structures were tested for several mechanical properties (porosity, compression and microhardness). Micro-structural analysis (electron microscopy and x-ray diffraction) was also performed on these samples, and these findings were correlated with results obtained from mechanical tests. The results indicate that there is a positive correlation between compression strength and sintering temperature and the optimal properties are obtained at a temperature of 1200 degrees C and a boron oxide bioglass doping content of 5 wt. %.
Keywords: Hydroxyapatite; Boroxide Containing Bioactive Bioglass; Sintering; Microstructure; Mechanical Properties; MECHANICAL-PROPERTIES; DIETARY BORON; GLASS; BONE; BHA